Exploring targeted preventive health check interventions - a realist synthesis - Nanna Bjørnbak Christoffersen; Freja Ekstrøm Nilou; Trine Thilsing; Lars Bruun Larsen; Jane Nautrup Østergaard; Marie Broholm-Jørgensen (BMC, 2023)
Abstract Background Preventive health checks are assumed to reduce the risk of the development of cardio-metabolic disease in the long term. Although no solid evidence of effect is shown on health checks targeting the general population, studies suggest positive effects if health checks target people or groups identified at risk of disease. The aim of this study is to explore why and how targeted preventive health checks work, for whom they work, and under which circumstances they can be expected to work. Methods The study is designed as a realist synthesis that consists of four phases, each including collection and analysis of empirical data: 1) Literature search of systematic reviews and meta-analysis, 2) Interviews with key-stakeholders, 3) Literature search of qualitative studies and grey literature, and 4) Workshops with key stakeholders and end-users. Through the iterative analysis we identified the interrelationship between contexts, mechanisms, and outcomes to develop a program theory encompassing hypotheses about targeted preventive health checks. Results Based on an iterative analysis of the data material, we developed a final program theory consisting of seven themes; Target group; Recruitment and participation; The encounter between professional and participants; Follow-up activities; Implementation and operation; Shared understanding of the intervention; and Unintended side effects. Overall, the data material showed that targeted preventive health checks need to be accessible, recognizable, and relevant for the participants' everyday lives as well as meaningful to the professionals involved. The results showed that identifying a target group, that both benefit from attending and have the resources to participate pose a challenge for targeted preventive health check interventions. This challenge illustrates the importance of designing the recruitment and intervention activities according to the target groups particular life situation. Conclusion The results indicate that a one-size-fits-all model of targeted preventive health checks should be abandoned, and that intervention activities and implementation depend on for whom and under which circumstances the intervention is initiated. Based on the results we suggest that future initiatives conduct thorough needs assessment as the basis for decisions about where and how the preventive health checks are implemented.